2018
DOI: 10.1038/s41409-018-0236-z
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab for the treatment of severe steroid-refractory acute graft-versus-host disease of the lower gastrointestinal tract

Abstract: Steroid-refractory (SR) acute gastrointestinal (GI) graft-versus-host disease (GVHD) is associated with significant mortality in allogeneic hematopoietic cell transplantation recipients. We retrospectively evaluated the efficacy of tocilizumab for the treatment of SR biopsy-proven acute lower GI GVHD in 16 consecutive adult transplant recipients between October 2015 and July 2016. Tocilizumab 8 mg/kg was administered every 2 weeks until achievement of complete response, defined as resolution of all manifestati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…51 Signal blockade of IL-6 is thought to block differentiation thereby reducing T-helper (Th) 1 and Th17 cell production while enhancing regulatory T cells, thus making it an ideal agent for prevention. 52 Early phase I/II data showed that by adding tocilizumab (day À1 only) to cyclosporine/methotrexate GVHD prophylaxis in HLA-matched unrelated and related allogeneic HCT recipients (N=48), incidence of acute GVHD II-IV was as low as 12%. 47 OS and progression-free survival at 2 years were 84% and 68%, respectively.…”
Section: Tocilizumabmentioning
confidence: 99%
See 3 more Smart Citations
“…51 Signal blockade of IL-6 is thought to block differentiation thereby reducing T-helper (Th) 1 and Th17 cell production while enhancing regulatory T cells, thus making it an ideal agent for prevention. 52 Early phase I/II data showed that by adding tocilizumab (day À1 only) to cyclosporine/methotrexate GVHD prophylaxis in HLA-matched unrelated and related allogeneic HCT recipients (N=48), incidence of acute GVHD II-IV was as low as 12%. 47 OS and progression-free survival at 2 years were 84% and 68%, respectively.…”
Section: Tocilizumabmentioning
confidence: 99%
“…74 Other small case series have reported on mixed, but promising, activity with partial and complete responses in heavily pretreated patients. 52,70,71 In addition, early administration of tocilizumab as first-line therapy following steroid refractoriness has also shown benefit, although mostly in patients with skin and/or GI involvement. 72 Likely the strongest argument for tocilizumab was reported in a retrospective case series 52 including 16 patients with only biopsy-proven GI-associated steroidrefractory acute GVHD.…”
Section: Tocilizumabmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to a few case reports (156158) and conference abstracts (159) only two published case series report the effects of tocilizumab in the treatment of acute steroid-refractory aGVHD (Table 7) (160, 161). Drobyski et al (161) described the effects in eight patients (two acute and two chronic GVHD) where tocilizumab was administered once every 3–4 weeks.…”
Section: Il-6 In Asct—clinical Datamentioning
confidence: 99%